Uncle Remus, his songs and his sayings - Harris, Joel Chandler, 1848-1908.; Hemenway, Robert E., 1941-2015. (New York : Penguin Books, 1982)
Presents the legends, songs, and sayings of Uncle Remus, following the text of the first edition of Joel Chandler Harris' attempt to record traditional black stories of his time.
Originally published: New York : D. Appleton, 1880.
Bibliography: p. 33-34.
Keywords: Remus, Uncle (Fictitious character) -- Literary collections; African Americans -- Folklore -- Literary collections; Animals -- Folklore -- Literary collections; African American men -- Literary collections; Plantation life -- Literary collections; Georgia -- Literary collections